2013
DOI: 10.1194/jlr.p040022
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase in plasma 4β-hydroxycholesterol concentration in patients after kidney transplantation

Abstract: This article is available online at http://www.jlr.org Phenotyping of cytochrome CYP3A seems to be of special importance because enzymes belonging to this family, particularly CYP3A4, are involved in the metabolism of more than 50% of currently prescribed drugs. However, the selection of an appropriate CYP3A phenotyping substrate and metric is still a matter of discussion, although some CYP3A test substrates, including midazolam, erythromycin, alprazolam, and nifedipine have been proposed ( 15 ). However, admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…Especially, 4β-hydroxycholesterol may be useful in patients with renal failure because the kinetics of 4β-hydroxycholesterol seem to be unaffected by renal function due to the slow elimination by 7α-hydroxylation [20]. We have previously reported a significant increase in plasma concentration of 4β-hydroxycholesterol as an endogenous marker of CYP3A activity in patients with end stage renal disease (ESRD) after kidney transplantation [21]. However, wide interindividual variability in the degree of increase was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, 4β-hydroxycholesterol may be useful in patients with renal failure because the kinetics of 4β-hydroxycholesterol seem to be unaffected by renal function due to the slow elimination by 7α-hydroxylation [20]. We have previously reported a significant increase in plasma concentration of 4β-hydroxycholesterol as an endogenous marker of CYP3A activity in patients with end stage renal disease (ESRD) after kidney transplantation [21]. However, wide interindividual variability in the degree of increase was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentration of 4β-hydroxycholesterol was determined using a gas chromatography/mass spectrometry (GC/MS) system according to the procedures that we reported previously [21]. One hundred μl of plasma sample was mixed with 20 μl of internal standard (1000 nM 4β-hydroxycholesterol-d7 in 2-propanol) and 200 μl of 2 M sodium methoxide solution in ethanol, and the mixture was left at room temperature for 20 min to convert esterified to free 4β-hydroxycholesterol.…”
Section: Measurement Of Plasma Concentration Of 4β-hydroxycholesterolmentioning
confidence: 99%
“…Plasma concentration of 4b-hydroxycholesterol was determined using a gas chromatography/mass spectrometry system according to the procedures that we reported previously (Suzuki et al, 2013). Inter-assay coefficients of variation for 20 and 200 ng/ml samples were 3.8% and 4.2%, respectively (n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, 4b-hydroxycholesterol is suitable for the evaluation of CYP3A activity in stable kidney transplant recipients. We defined stable kidney transplant recipients as those who underwent transplantation more than 90 days prior to the study, because we have previously shown in patients with end-stage renal disease that plasma concentration of 4b-hydroxycholesterol becomes stable 90 days after kidney transplantation (Suzuki et al, 2013). Dowling et al (2003) used the erythromycin breath test and showed that CYP3A activity in patients with end-stage renal disease was significantly lower than that in controls.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation